EFFECT OF RISK ANALYSIS ON PERFORMANCE OF FINANCIAL INSTITUTIONS - Kiprop, Lagat Fredrick; Yegon, Josephat (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of the study was to determine the effect of risk analysis on performance of financial institutions. Methodology: The study used explanatory research design. The study used stratified random sampling to select respondents from target population comprising of managers of 46 commercial banks, 52 Micro Finance institutions (MFIs) and 200 SACCOs and a sample size of 239 respondents obtained. Data was collected using questionnaires. Descriptive statistics was presented, while inferential statistics was done using Pearson product moment correlation. Results: The risk analysis had positive relationship with the performance of financial institutions. Unique contribution to theory, practice and policy: considerations due to the complexity of the financial sector nowadays makes it necessary before any policy analysis should rely upon different indicators and mainly upon those that reflect the whole reality of the industry performance and explicitly consider and carefully impose some regulations that consider different characteristics of ownership structure of financial institutions and the level of risk tolerance. Key words: Risk analysis, performance, financial institutions